Validation study for the Academic Maladjustment Questionnaire on a Romanian sample - Cazan, Ana-Maria; Stan, Maria Magdalena; Clinciu, Aurel Ion; Truţa, Camelia; Maican, Catalin Ioan (Frontiers in Psychology, 2023)
The problem of academic dropout in the first year of studies represents an important issue for higher education, in that it accounts for an important indicator of quality but also for the negative consequences it produces on individual, institutional and social level. The main aim of the study is to validate and evaluate a robust measure of overall academic maladjustment. The participants were 809 first-year students from various Romanian universities. The results showed a reliable version of the instrument with a factorial structure that did not deviate significantly from the authors' initial model. The exploratory and confirmatory factor analysis revealed a unified score including six dimensions, procrastination, dishonestyunethical behavior, test anxiety, machiavellian attitude, neuroticism and somatisation. Our results confirmed that besides academic achievement, personal factors are important indicators of adjustment, showing that personal resources management, emotional and behavioral strategies are components of adjustment. Our study revealed a medium and positive correlation between overall maladjustment and academic dropout intention, procrastination seemed to be the most relevant predictor of dropout intention. Academic adjustment acts as a safeguard against dropping out, and it is crucial to acknowledge that most students enter college with the intention of completing their studies.